Incidência e avaliação da atividade lipolítica e proteolítica de Bacillus cereus em leite UHT - Maziero, Maike Taís; Viana, Cibeli [UNESP]; Montanhini Neto, Roberto; Pinto, José Paes de Almeida Nogueira [UNESP]; Bersot, Luciano dos Santos (My University, 2011)
Bacillus cereus is a thermoduric microorganism that may has lipolytic and proteolytic activity, decreasing the quality of dairy products by causing sensorial defects during shelf life. The presence of B. cereus was evaluated in 110 UHT milk samples from 19 commercial brands, using two methods: qualitative and quantitative. By the quantitative technique no sample had any counts above the limit of detection (> 10 CFU/ml). On the other hand, by the qualitative method 18 samples (16.36%) were positive for B. cereus. All strains of B. cereus isolated from UHT milk showed proteolytic activity after 24h incubation. Any isolated strain had lipolytic activity after 24h of incubation, however, extending this incubation to 96h, 10 strains formed characteristic lipolysis sign in growth medium. It was found that 44.4% B. cereus strains presented both lipolytic and proteolytic activity.

Bacillus cereus é um microrganismo termodúrico que pode apresentar atividade lipolítica e proteolítica, comprometendo a qualidade de produtos lácteos. Sua presença foi avaliada em 110 amostras de 19 marcas comerciais através de duas metodologias, uma qualitativa e outra quantitativa. Pela técnica quantitativa nenhuma amostra apresentou contagens acima do limite de detecção do método (>10 UFC/ml). Já pelo método qualitativo 18 amostras (16,36%) foram positivas para B. cereus. Todas as cepas de B. cereus isoladas em leite UHT apresentaram atividade proteolítica após 24h de incubação. Nenhuma das cepas de B. cereus apresentou atividade lipolítica após 24h de incubação, no entanto, prolongando esta incubação para 96h, dez cepas formaram halos característicos de lipólise. Foi constatado que 44,4% das cepas de B. cereus apresentaram atividade lipolítica e proteolítica simultaneamente. A presença de B. cereus proteolítico e lipolítico em leite UHT pode causar defeitos sensoriais durante seu prazo de validade.
Incidence and lipolytic and proteolytic activity of Bacillus cereus in UHT milk
Keywords: Lipolysis; Proteolysis; Gelation; Lipólise; Proteólise; Geleificação